2018
DOI: 10.1007/s00436-018-5933-4
|View full text |Cite
|
Sign up to set email alerts
|

Helminth fauna of Megaleporinus obtusidens (Characiformes: Anostomidae) from Lake Guaíba: analysis of the parasite community

Abstract: Structure of the helminth community of Megaleporinus obtusidens collected in Lake Guaíba was evaluated, and the results indicated that the diversity of helminth species was probably determined by fish behavior and eating habits. The influence of sex, weight, and standard length of hosts for parasitic indices was also analyzed. Sixteen helminth species were found parasitizing M. obtusidens, including the following: platyhelminths, with the highest richness, represented by one species of Aspidobothrea; four spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…Furthermore, while Wendt et al (2015) stated that the terminal projection of the accessory piece described in the original description by Kritsky et al (1980) was absent, this characteristic was observed in the present study. In addition, the morphology of the vaginal aperture in the present study is different to that described by Wendt et al (2015) [see Figure 2d in Wendt et al (2015)], and is more closely related to that represented by Karling et al 2014[see Figure 3 in Karling et al (2014]. Wendt et al (2015) stated that the ventral bar is V-shaped, but in fact it is the dorsal bar that has this shape, as described by Kritsky et al (1980) and confirmed by Karling et al (2014).…”
Section: Remarkssupporting
confidence: 53%
See 4 more Smart Citations
“…Furthermore, while Wendt et al (2015) stated that the terminal projection of the accessory piece described in the original description by Kritsky et al (1980) was absent, this characteristic was observed in the present study. In addition, the morphology of the vaginal aperture in the present study is different to that described by Wendt et al (2015) [see Figure 2d in Wendt et al (2015)], and is more closely related to that represented by Karling et al 2014[see Figure 3 in Karling et al (2014]. Wendt et al (2015) stated that the ventral bar is V-shaped, but in fact it is the dorsal bar that has this shape, as described by Kritsky et al (1980) and confirmed by Karling et al (2014).…”
Section: Remarkssupporting
confidence: 53%
“…This description was based on a single specimen and presents sclerotized structures of the haptor and MCO only. Two redescriptions of T. parvus were recently proposed and added new data on the morphology of internal organs such as the position of the vagina, testis, ovary, seminal vesicle and the egg morphology (Karling et al 2014, Wendt et al 2015. However, some morphological differences were observed in relation to these previous descriptions and they are presented herein to correct and complement the diagnosis of T. parvus.…”
Section: Remarksmentioning
confidence: 90%
See 3 more Smart Citations